Data-Driven Evaluation of Metaverse Integration in Healthcare Education: User Adoption Readiness and Impact on Clinical Competency among Healthcare Professionals - SHAIKH, KHAIRUNISA; ABIDEEN, ZAIN-UL-; RASHEED, TAHIRA; SAFDAR, RUKKIA; HABIB, MUHAMMAD ZUBAIR (Pakistan Journal of Medical & Health Sciences, 2026)
Background: One of the new methods of change in healthcare and higher education is the integration of metaverse technologies such as virtual reality, augmented reality and mixed reality. The traditional medical training has been found to have challenges of poor access to clinical practice, patient safety issues, ethical issues and health practitioners’ shortage. Objective: To assess the applicability of metaverse technologies in medical education assessing both the willingness of medical workers to implement immersive learning devices and the effects of training with the help of metaverse on clinical performance results. Methodology: This quantitative study was carried out at Healthcare Institution in Sind, Pakistan from 1st January 2024 to 30th June 2025. Adoption element entailed 383 recruited healthcare professionals and students who were recruited through stratified sampling. The perceptions, behavioral intention, and determinants of adoption were measured using a structured questionnaire which was prepared according to Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). The quasi-experimental design with clinical effectiveness assessment was performed with regard to an experimental group (metaverse based training, n= 26) and a control group (traditional training, n= 30). Results: The respondents showed favorable attitudes toward the adoption of the metaverse, and the following were found to be the major influencing attitude factors, namely, performance expectancy (M=3.86), hedonic motivation (M = 3.83), and personal innovativeness (M=3.77). Compared influence was seen in social influence as well as in perceived privacy. Overall, OSCE scores in the experimental and control groups were significantly higher in all the stations namely; spinal injury transport, treatment of composite injuries, CPR and tracheal intubation, and bronchoscopic lung segment recognition (80.31±11.15 vs. 70.50±10.76; p = 0.002), treatment of composite injuries, CPR and tracheal intubation (87.17±5.74 vs. 77.30±11.45 Conclusion: Immersive learning through metaverse proved to be very acceptable and clearly enhanced clinical competency, compared to conventional approaches to training. These results substantiate the idea of the inclusion in the academic toolset of immersive technologies to optimize clinical skills training and overcome the shortcomings of the traditional health care training systems.